Influence of the Nanostructure of Palladium Mesoparticles on the Kinetics of Molecular Oxygen Electroreduction - Hernández Creus, A. (2004)
The effect of the nanostructure of electrodeposited palladium mesoparticles on the oxygen electroreduction reaction (oerr) in acid media is studied by electrochemical techniques combined with scanning tunneling microscopy, tapping-mode atomic force microscopy, and scanning electron microscopy. Palladium mesoparticles supported on highly oriented pyrolytic graphite (HOPG) exhibit a remarkable electrocatalytic enhancement, i.e., a decrease in the cathodic overvoltage on the order of 0.25 V, as compared to polycrystalline palladium electrodes. For a similar particle size, the largest electrocatalytic activity is obtained by use of quasi-twodimensional (2D) ramified palladium particles and electrodeposited palladium charges exceeding 3 mC cm-2. For these particles, experimental results show that the electrocatalytic enhancement of the oerr can be related to the combined influence of the nanostructure of 2D branching on the HOPG and traces of oxygen-containing adsorbates that induces local perturbation of electronic states at palladium mesoparticles. The 2D nature of surfaces increases markedly the reversibility of the first two-electron-transfer step of the oerr.